Potrzeba stosowania rachunkowości zarządczej w kontekście wdrażania controllingu w zakładzie ubezpieczeń - Chmielowiec-Lewczuk, Magdalena (The Need of Management Accounting Application in Context of Controlling Implication in Insurance Company, 2005)
The insurance company is specific financial institution which is characterized of such features as insurance product, financial policy, different costs calculation, reinsurance and investment activity. Management accounting application is closely connected with controlling implication because management gives information for controlling. Management accounting is one of a part the whole accounting system, but its main aim is to complete financial accounting. The main aim of controlling is to helps management be better. In insurance company may exist management accounting without controlling but not inversely, controlling always needs management accounting to exist. This system of accounting finds application in such different areas of controlling as personal controlling, financial controlling, marketing and sale controlling and quality controlling.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 112-119